Co-movement among sectoral stock market indices and cointegration among dually listed companies - Ramin Cooper Maysami; Loo, Sze Wee; Koh, Tat Koon (Penerbit Universiti Kebangsaan Malaysia, 2004)
This paper analyzes the co-movement between sectoral stock indices of the US and Singapore, through examining whether the S&P 500 Electronics (Semiconductor) Price Index leads Stock Exchange of Singapore's Electronics Price Index. The article also examines price co-movement of stocks listed dually in Singapore and the US. Using Johansen's (1988) Vector Error Correction Model (VECM), the paper concludes the existence of long-run cointegrating relationship both between the US and Singapore electronic sectors in general, and more specifically among the three dually listed stocks under consideration. However, the results point to a short-term disequilibria in the prices of dually listed stocks, leading to the conclusion that short-run arbitrage opportunities may exist.